Artificial intelligence vs human designers: partners or competitors (JÓVENES EN LA CIENCIA, 2024)
The study explores the processes of generating images using artificial intelligence products DALL-E 2 and Midjourney with the aim of understanding the impact of Artificial Intelligence on designers' work. To reinforce the conclusions, a series of images were generated across various prompts in Midjourney).